Cascade Release Nanocarriers for the Triple-Negative Breast Cancer Near-Infrared Imaging and Photothermal-Chemo Synergistic Therapy - Li, Ke; Li, Ruyue; Zhou, Baona; Chen, Jing; Lan, Kai; Zhan, Wenhua; Chen, Di; Zhang, Tao; Li, Xueping (Frontiers in Oncology, 2021)
Triple-negative breast cancer (TNBC) has inadequate treatment approaches and a poor prognosis. It is urgent to develop new treatment approaches for TNBC. The combination of photothermal therapy (PTT) and chemotherapy is a very effective potential therapy for TNBC. However, asynchronous accumulation, unclear efficacy, and toxic side effects hinder the further promotion of this method. Therefore, we designed and constructed a new type of nanocarriers, the cascade release near-infrared imaging (NIFI) & thermal-chemo combination nanoparticles (CNC NPs), that can release drugs through the cascade of ultrasound triggering and pH responding to achieve the synchronous tumor accumulation, monitoring and synergistic treatment of two functional molecules. The key material of CNC NPs is the polydopamine (PDA), which, through self-assembling, forms a rigid shell that contains doxorubicin (DOX) and NIF fluorescent dye IR780 on the surface of the perfluorohexane (PFH) microbubbles. The results show that CNC NPs have a hollow core-shell structure with an average particle size of 97.3±27.2 nm and have exceptional colloidal stability and photothermal conversion efficiency. The NPs can effectively perform cascade drug release through ultrasound triggering and pH responding. CNC NPs have good in vivo biological safety and excellent fluorescence imaging, drug delivery, and therapeutic abilities in the TNBC models. These results provide an experimental basis for the development of new clinical treatment methods for TNBC.